Diversion in Juvenile Criminal Investigations: A Study in the Surabaya District Court Jurisdiction - Rizky Permana Putra; Prasetijo Rijadi (Fakultas Hukum Universitas Bhayangkara Surabaya, 2025)
Protection of children in conflict with the law has been regulated under Law No. 23 of 2002 on Child Protection and Law No. 3 of 1997 on Juvenile Justice. However, its implementation in practice still faces various obstacles, particularly in handling children in conflict with the law. Diversion and restorative justice have emerged as alternative approaches for resolving juvenile cases, with the police serving as the primary investigator through the exercise of discretionary authority. This study aims to analyze the factors underlying the implementation of diversion, the strategic role of investigators in its implementation, as well as the obstacles and impacts that arise during the diversion process. The research employs both normative and sociological juridical approaches to obtain an in-depth understanding of diversion practices. Primary data were obtained through in-depth interviews with police officers, correctional facility officers, NGO activists, and academics in the field of child protection, while secondary data were collected through a literature review of statutory regulations, books, journals, and various related literature. Data were analyzed qualitatively to provide a comprehensive overview of diversion practices within the juvenile criminal justice system in Indonesia. The research findings indicate that diversion can be implemented through the role of investigators, with the positive impact of restoring social relationships between victims and perpetrators. However, the implementation of diversion still faces structural and cultural barriers, including a lack of awareness among investigators and the public, as well as insufficient supporting facilities.